O PAPEL DAS NOVAS TECNOLOGIAS DE MASSA NO CAMPO DO ADVOCACY (Revista Paradigma, 2022)
The objective of this work, through bibliographical research, is to follow a logical path, tracing a diagnosis of the changes that have occurred over the years for the implementation of public policies. Displays the Advocacy and Lobby concepts, functions, and differences. It analyzes the role of new mass technologies in the context of disseminating advocacy action information. It discusses the importance of advocacy strategies for the effective participation of civil society in the public sector. In the end, it exposes the relation of law to advocacy and its expansion through technology, using the inductive method.